2019
DOI: 10.1111/crj.13024
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima‐media thickness in chronic obstructive pulmonary disease and survival: A multicenter prospective study

Abstract: Introduction Chronic obstructive pulmonary disease (COPD) is associated with increased cardiovascular morbidity and mortality. Carotid intima‐media thickness (CIMT) is a noninvasive method assessing atherosclerosis. Objective It was aimed to determine relationship and survival between COPD and CIMT. Methods CIMT was measured using Doppler ultrasound (USG) in 668 stable COPD patients at 24 centers. Patients were followed‐up for 2 years. Results There were 610 patients who completed the study. There were 200 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our analysis of Gulbas [19] endorsed our data by showing important variations in the baseline characteristics of groups such as era, smoking load (pack-years), forced vital ability (FVC) (percent), FEV1 (percent), FEV1/FVC and hypertension (years) variables (P < 0,05). There were 200 CIMT <0.78 mm (group 1) and 410 CIMT <0.78 mm (group 1) (group 2).…”
Section: Discussionsupporting
confidence: 78%
“…Our analysis of Gulbas [19] endorsed our data by showing important variations in the baseline characteristics of groups such as era, smoking load (pack-years), forced vital ability (FVC) (percent), FEV1 (percent), FEV1/FVC and hypertension (years) variables (P < 0,05). There were 200 CIMT <0.78 mm (group 1) and 410 CIMT <0.78 mm (group 1) (group 2).…”
Section: Discussionsupporting
confidence: 78%
“…A previous study made by Zureik et al also reported a significant relationship between decreased FEV1 levels and endothelial dysfunction and vascular wall stiffness and the presence of atherosclerosis. Additionally, CIMT was found to be significantly associated with GOLD‐combined assessment groups as stated by Gulbas et al Although previous studies reported no relationship between COPD exacerbations and CIMT, it has also been suggested by Golpe et al that the increased systemic inflammatory response during exacerbations may contribute to the activation of an atherosclerotic process 48–51 . Ambrosino et al found that the risk of carotid plaque development was directly correlated with GOLD‐combined assessment groups in COPD patients 52 …”
Section: Discussionmentioning
confidence: 83%
“…Additionally, CIMT was found to be significantly associated with GOLDcombined assessment groups as stated by Gulbas et al Although previous studies reported no relationship between COPD exacerbations and CIMT, it has also been suggested by Golpe et al that the increased systemic inflammatory response during exacerbations may contribute to the activation of an atherosclerotic process. [48][49][50][51] Ambrosino et al found that the risk of carotid plaque development was directly correlated with GOLD-combined assessment groups in COPD patients. 52 Laboratory investigations revealed a significant elevation of serum inflammatory markers including CRP, fibrinogen, amyloid A, and IL6 in COPD patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and development of this disease are closely related to abnormal in ammation caused by harmful substances and cardiovascular disease [3,4] . The occurrence of COPD can lead to the decrease of vascular endothelial function, the increase of carotid intima-media thickness, the formation of atherosclerotic plaque and the increase of arterial stiffness, thus increasing the incidence of cardiovascular events [5] . Arterial stiffness is an independent risk factor for evaluating and predicting cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%